THE INCONVENIENT PROBLEMS OF LAW ENFORCEMENT IN INDONESIA IN RELATION TO THE CASE OF BIBIT-CHANDRA - KS, R.A Rahadjeng Endah (UI Scholars Hub, 2021)
In this article, the author presents a description and analysis of recent developments in Indonesian law enforcement. The leaders of Corruption Eradication Commission (KPK), Bibit S. Rianto and Chandra M. Hamzah, are currently facing legal problems. Both have been accused of abuse of authority by issuing a travel ban letter preventing Anggoro Wodjojo and Joko Tjandra from leaving Indonesia. In addition, the two KPK leaders are also accused of corruption. In the following process of police investigation, Bibit S. Rianto and Chandra M. Hamzah were arrested by the police. Legal proceedings against Bibit S. Rianto and Chandra M. Hamzah then became a national issue, and the two accused gained support from people throughout Indonesia. Efforts to arrest Bibit S. Rianto and Chandra M. Hamzah were regarded as an attempt to criminalize the Corruption Eradication Commission (KPK). In order to quell increasingly vocal protests, President Susilo Bambang Yudhoyono formed an independent fact-finding team to make clarifications in connection with the case of Bibit S. Rianto and Chandra M. Hamzah. The independent team delivered recommendations to President Susilo Bambang Yudhoyono calling for an immediate stop to the investigation against Bibit S. Rianto and Chandra M. Hamzah, among others, by reason of insufficient evidence. This case then ended with the issuance of a Termination of Prosecution Assessment Letter (Surat Ketetapan Penghentian Penuntutan (SKPP)) from the Attorney General of the Republic of Indonesia.